Co-occurrence of germline BRCA1 and CDH1 pathogenic variants. Issue 6 (23rd June 2020) - Villy, Marie-Charlotte; Mouret-Fourme, Emmanuelle; Golmard, Lisa; Becette, Véronique; Callet, Nasrine; Marx, Gilles; Colas, Chrystelle; Lamarque, Dominique; Rouleau, Etienne; Stoppa-Lyonnet, Dominique
Abstract : Introduction: We report a very rare case of familial breast cancer and diffuse gastric cancer, with germline pathogenic variants in both BRCA1 and CDH1 genes. To the best of our knowledge, this is the first report of such an association. Family description: The proband is a woman diagnosed with breast cancer at the age of 52 years. She requested genetic counselling in 2012, at the age of 91 years, because of a history of breast cancer in her daughter, her sister, her niece and her paternal grandmother and was therefore concerned about her relatives. Her sister and maternal aunt also had gastric cancer. She was tested for several genes associated with hereditary breast cancer. Results: A large deletion of BRCA1 from exons 1 to 7 and two CDH1 pathogenic cis variants were identified. Conclusion: This complex situation is challenging for genetic counselling and management of at-risk individuals.